Biosorption of Cu2+, Cd2+, Pb2+, and Zn2+ using dried marine green macroalga Caulerpa lentillifera - Prasert Pavasant (2018)
The sorption of Cu2+, Cd2+, Pb2+, and Zn2+by a dried green macroalga Caulerpa lentillifera was investigated. The removal efficiency increased with pH. The analysis with FT-IR indicated that possible functional groups involved in metal sorption by this alga were O-H bending, N-H bending, N-H stretching, C-N stretching, C-O, S{double bond, long}O stretching, and S-O stretching. The sorption of all metal ions rapidly reached equilibrium within 20 min. The sorption kinetics of these metals were governed by external mass transfer and intraparticle diffusion processes. The sorption isotherm followed the Langmuir isotherm where the maximum sorption capacities was Pb2+> Cu2+> Cd2+> Zn2+. © 2005 Elsevier Ltd. All rights reserved.